The copper-associated protein STEAP2 correlated with glioma prognosis and immune infiltration - Wang, Xu; Han, Mingzhi; Chen, Songyu; Sun, Yanfei; Tan, Ruirong; Huang, Bin (Frontiers in Cellular Neuroscience, 2022)
High-grade glioma is characterized by cell heterogeneity, gene mutations, and poor prognosis. Abnormal copper homeostasis affects the pathogenesis of glioma, but the underlying mechanisms and involved proteins are unknown. Here, we selected 90 copper-related proteins and verified their expression differences in glioma and normal tissues in the TCGA cohort followed by GO and KEGG clustering analyses. We then developed and validated a prognostic model. Moreover, we examined the mutation burden of copper-related proteins and discussed the differences in the immune microenvironment in the high- and low-risk groups. Furthermore, we focused on STEAP2 and demonstrated that STEAP2 expression was relatively low in tumor tissues compared to normal tissues, implying a favorable prognosis. Our findings provide a foundation for future research targeting copper-related proteins and their immune microenvironment to improve prognosis and responses to immunotherapy.